Skeletal Muscle Metastasis From Renal Cell Carcinoma: A Case Series and Literature Review - Sun, Juan; Zhang, Zimu; Xiao, Yu; Li, Hanzhong; Ji, Zhigang; Lian, Penghu; Zhang, Xuebin (Frontiers in Surgery, 2022)
Objectives: Skeletal muscle metastasis (SMM) from renal cell carcinoma (RCC) has been rarely reported. This case series was performed to increase clinicians’ understanding of its clinical features and treatments. Methods: We evaluated the clinical presentations, diagnoses, and treatments of 2 patients with SMM from RCC in our hospital and 39 cases reported in the literature. Results: Among the 41 patients, 4 (9.76%) were females and 37 (90.24%) were all males. The average age was 60.5±12.6 years old (range from 7 to 81). The size of tumors varied from 1cm to 28cm. And metastatic sites of 6 (14.63%) cases were in the heads, 20 (48.78%) in the limbs, 9 (21.95%) in the trunks, 3 (7.32%) in the buttock and the other 3 (7.32%) were multiple sites. The mean of intervals between the RCC and the discovery of the first SMM was 73.61 months. More than half of patients (25, 60.98%) were diagnosed by MRI and 25 (60.98%) patients performed biopsy of the mass to establish the diagnosis. Finally, 30 (73.17%) cases performed mass excision. Then the adjuvant therapy was performed in 18 patients including immunotherapy, radiotherapy, chemotherapy and targeted therapy. The median follow-up after SMM was 9 months (P25, P75: 5, 23) in which the longest survival time of patients with SMM of RCC was 8 years while the shortest was only 3 months. Conclusion: SMM should always be considered in patients with RCC, even well after primary treatment. The clinical manifestation generally involves a long history of asymptomatic masses or swelling. Magnetic resonance imaging (MRI) may be more effective and recommended for the diagnosis of those suspected masses. The recommended managements include rapid biopsy of the suspected lesions, identification of sites of other metastasis, resection of the metastatic masses and systemic treatment.